(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract: The research sought to identify the crises that occurred during the research period and their reflection on the performance of the hotel Research sample as well as to identify the reality of auditing the hotel Research sample and the preparation of a performance audit program can be adopted in auditing the performance of hotels in light of crises, and the problem of the research lies in the lack of a program to audit the performance of hotels that takes into account the crises experienced by the hotel sector, The research was based on solving its problems on three hypotheses, the first is that the performance audit in light of the Covid-19 pandemic was reflected on the result of the hotel’s activity in the research sample, the second was reflected in the change in the exchange rate of the dollar against the Iraqi dinar on the hotel’s activity, and the third there are other factors that affected the performance of the hotel and reflected on the result of the activity. The researcher reached a set of results, the most important of which is the need for the hotel to rely on the indicators and programs prepared by the Federal Financial Supervision Bureau and to conduct a performance evaluation of its activity to diagnose weaknesses and work to address them in a way that contributes to reducing the risks of crises and ensuring the efficiency and effectiveness of the activity.